THE ROLE OF THE TEACHER IN IMPLEMENTING THE ATTITUDE OF RELIGIOUS TOLERANCE IN CLASS IV ELEMENTARY SCHOOL - Choirul Anwar, Awiria, Yosi Gumala (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
The study conducted in the fourth grade of elementary school regarding the role of teachers in instilling an attitude of religious tolerance in students. This research was conducted because of the phenomenon of intolerance that occurred and the awareness of the importance of religious tolerance because there had been cases of intolerance related to religion. The purpose of this study was to find out how the teacher's role in instilling an attitude of religious tolerance in elementary school. The research method used was a qualitative approach with descriptive qualitative methods. research in the form of observations and interviews as well as documentation related to the role of teachers in instilling an attitude of religious tolerance. The result of the research that has been done is that the teacher plays a good role in instilling an attitude of religious tolerance. Inculcating an attitude of religious tolerance to students such as teaching attitudes, not cornering students, the ability to motivate in various ways ,and giving real examples in everyday life. The conclusion obtained from the research that has been done is that teachers play a role in instilling religious tolerance in students so that students can apply the values of religious tolerance in schools.